PEMBINAAN NARAPIDANA PEREMPUAN DI LEMBAGA PEMASYARAKATAN KELAS IIB ANAK AIR KECAMATAN KOTO TANGAH KOTA PADANG - Syafrida; Afnibar; Wakidul Kohar (JURNAL ILMIAH RESEARCH STUDENT, 2023)
Abstract. Correctional institutions should be able to carry out their functions optimally, namely making prisoners become better human beings after serving a period of detention, but in reality this hope has not been realized optimally. The aim of the research is to determine the forms of development of female convicts. This type of research is descriptive field research. Data collection techniques are observation, interviews and documentation. The research results show that there are 2 forms of coaching, namely first, independence coaching, second, spiritual or religious coaching. The material for religious formation is learning Tahsin al-Qur'an, Tahfiz, the areas of aqidah, worship and morals. Direct interaction coaching methods, persuasive coaching, planned coaching, individual and group approaches. Padang Class IIB Women's Penitentiary has held a Joint Commitment Signing and signing of cooperation with stakeholders related to the implementation of the main tasks and functions of Corrections, namely with the Regional Office of the Ministry of Religion of West Sumatra Province, the Office of the Ministry of Religion of Padang City, the Padang Education and Training Center and Bung Hatta University in Padang .